Effects of recovered brown alumina filler loading on mechanical, hygrothermal and thermal properties of glass fiber–reinforced epoxy polymer composite. Issue 9 (November 2021) - Sabarinathan, P; Annamalai, VE; Rajkumar, K; Vishal, K
This study investigates the efficiency of recovered brown alumina (RBA) particles filled in epoxy glass-fiber composites. The RBA particles were obtained from grinding wheel rejects with the help of the mechanical crushing process. Recovered particles finer than 120 grit were used as particulate filler for composite preparation. Composites were processed through a hand-layup technique by varying RBA filler loading percentages (0, 5, 10, 15, and 20 wt.%) in a glass fiber–reinforced epoxy matrix. Physical, mechanical, water absorption, and thermal properties of the composites were tested experimentally. By suitable addition of RBA, it is possible to tailor the shore-D hardness, tensile modulus, flexural strength, flexural modulus, and maximum degradation temperature. The 20%-filled RBA composite shows the maximum flexural strength of 382 MPa, and the shore-D hardness value was 85. The fracture surface shows a failure mechanism dominated by matrix cracking and debonding of fiber/particles from the interface. Hygrothermal testing of the RBA20-filled composite reveals 9% and 4% reduction in tensile and flexural properties. The thermal stability of the glass fiber–reinforced composite improves as the filler percentage increases. Maximum thermal stability of 435°C was observed in 20%-filled RBA polymer composite.